From Marikana to #feesmustfall: The Praxis of Popular Politics in South Africa. (May 2016) - Naicker, Camalita
This article explores the forms of popular politics that rose out of massive student protests in South Africa at the end of 2015. By delving deeper into the way higher education has been structured in post-apartheid South Africa, the author explains the ways in which race and class privilege have been reified in South African universities. The spatial location of the university within South Africa and the place of the university within the African continent is not reflected in institutional culture of higher education but is deeply embedded in the student protests. By exploring the collective decision making structures of students the author explores students growing lack of faith in higher education institutions to effect any transformational change.